2009
DOI: 10.1111/j.1365-277x.2009.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary management of women with polycystic ovary syndrome in the United Kingdom: the role of dietitians

Abstract: Background Polycystic ovary syndrome (PCOS) is a common endocrine condition associated with hyperandrogenism, infertility and metabolic dysfunction. Weight management through diet and lifestyle modifications are fundamental to its management, however, presently there are no official dietary guidelines. This study aimed to explore the dietary and lifestyle strategies followed by women with PCOS and the contribution of dietitians to its management. Methods A questionnaire was completed by 105 UK dietitians focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
8
53
3
1
Order By: Relevance
“…The current study suggests that women with PCOS may be more active than previously reported, with 74% self reporting that they did at least 30 min of moderate intensity activity per day, compared with Humphreys and Costarelli (2008), who reported that only 41% of women with PCOS reported undertaking moderate intensity exercise at least once per week. Additionally the Department of Health (2004) has reported that only 24% of women in the general population are sufficiently active to gain any health benefit, the higher rate of activity reported by the current study cohort may be explained by the reported benefits of physical activity improving some of their PCOS symptoms (Jeanes et al, 2009). However, of concern, 52% of overweight or obese women with PCOS were not achieving sufficient activity of 60 min per day to promote weight loss.…”
Section: Recommendation For Weight Management For Overweight Women Wicontrasting
confidence: 49%
See 4 more Smart Citations
“…The current study suggests that women with PCOS may be more active than previously reported, with 74% self reporting that they did at least 30 min of moderate intensity activity per day, compared with Humphreys and Costarelli (2008), who reported that only 41% of women with PCOS reported undertaking moderate intensity exercise at least once per week. Additionally the Department of Health (2004) has reported that only 24% of women in the general population are sufficiently active to gain any health benefit, the higher rate of activity reported by the current study cohort may be explained by the reported benefits of physical activity improving some of their PCOS symptoms (Jeanes et al, 2009). However, of concern, 52% of overweight or obese women with PCOS were not achieving sufficient activity of 60 min per day to promote weight loss.…”
Section: Recommendation For Weight Management For Overweight Women Wicontrasting
confidence: 49%
“…), weight (Is your weight stable?) and any PCOSrelated nutritional advice received (Supplementary Data 1; Jeanes et al 2009). Food diary data were entered into the dietary analysis software package Dietplan 6.3 (Forestfield Software, Horsham, UK) by a registered dietitian.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations